Perancangan Ergonomi Dalam Keselamatan Dan Kesehatan Kerja: Kajian Literature Review - Firmansyah, Rangga; Kurnia, Hibarkah; Nugroho, Irvan; Kennedy, John; Safi'i, Ahmat (JURNAL TEKNIK INDUSTRI, 2023)
Occupational Safety and Health is an effort to create a safe and comfortable work environment, but based on BPJS Employment 2020 data, the number of work accident cases reached 153,044. Reports on the number of work accidents in Indonesia still require action to prevent and deal with work accidents with the existence of dangers that can affect work accidents in the manufacturing industry in Indonesia. The aim of this research is to analyze and provide an overview of hazard identification, risk assessment and risk control for each job in the manufacturing industry in Indonesia. This research method is carried out starting from collecting articles, reducing articles, displaying discussion articles and conclusions using literature review studies. The data source used is national journal articles in the last 10 years (2013-2022). The results of this research found that the most research publication years are 2022 and 2020 with 5 articles each. Based on the type of industry, the most common type of industry is in the service sector with 10 articles. The contribution of this study is to facilitate other research as a reference for articles on K3 and ergonomics.